KONTAMINASI MERKURI (Hg) PADA PURUN TIKUS (Eleocharis dulcis) YANG TUMBUH DI TANAH SULFAT MASAM KECAMATAN ALALAK, KABUPATEN BARITO - Noor Azizah (Bioscientiae, 2009)
This research is aim to determine the content of mercury ( Hg) on  Purun tikus ( Eleocharis dulcis) that growth in acid sulphate soil. Executed in September-Nopember 2008, with the time interval of intake of sampel two week once. Sampling located on Kecamatan Alalak Kabupaten Barito Kuala and in Tungkaran (Martapura). Spectrometer Atom Absorption (SSA) is used as a tool to analysed content of mercury (Hg) at the Purun tikus sample. Data obtained in the form primary and secondary data that deskriftif analysed. At the root; the mercury content at week 1, 2, and 3 is 0,49 mg.kg-1, 2,10 mg.kg-1 and 1,90 mg.kg-1. Respectelly on the branch is 0,20 mg.kg-1, 1,80 mg.kg-1 and 1,54 mg.kg-1. Result of mercury analysed in the Purun tikus root and branch that growth on Tungkaran (Martapura) is respectelly 0,96 mg.kg-1dan 0,89 mg.kg-1. mercury on the root is higher that on the branch.